GRAPHITE-SULFIDE DEPOSITS IN RONDA AND BENI BOUSERA PERIDOTITES (SPAIN AND MOROCCO) AND THE ORIGIN OF CARBON IN MANTLE-DERIVED ROCKS - Crespo E.; Luque F.J.; Rodas M.; Wada H.; Gervilla F. (My University, 2006)
This paper describes unusual graphite-sulfide deposits in ultramafic rocks from the Serranía de Ronda (Spain) and Beni Bousera (Morocco). These deposits occur as veins, stockworks and irregular masses, ranging in size from some centimeters to a few meters in thickness. The primary mineral assemblage mainly consists of Fe-Ni-Cu sulfides (pyrrhotite, pentlandite, chalcopyrite and cubanite), graphite and chromite. Weathering occurs in some sulfide-poor deposits that consist of graphite (up to 90%), chromite and goethite. Texturally, graphite may occur as flakes or clusters of flakes and as rounded, nodule-like aggregates. Graphite is highly crystalline and shows light carbon isotopic signatures (δ13C≈- 15‰ to -21‰). Occasionally, some nodule-like graphite aggregates display large isotopic zoning with heavier cubic forms (probably graphite pseudomorphs after diamond with δ13C up to - 3.3‰) coated by progressively lighter flakes outwards (δ13C up to - 15.2‰). Asthenospheric-derived melts originated the partial melting (and melt-rock reactions) of peridotites and pyroxenites generating residual melts from which the graphite-sulfide deposits were formed. These residual melts concentrated volatile components (mainly CO2 and H2O), as well as S, As, and chalcophile elements. Carbon was incorporated into the melts from the melt-rock reactions of graphite-bearing (formerly diamonds) garnet pyroxenites with infiltrated asthenospheric melts. Graphite-rich garnet pyroxenites formed through the UHP transformation of subducted kerogen-rich crustal material into the mantle. Thus, graphite in most of the studied occurrences has light (biogenic) carbon signatures. Locally, reaction of the light carbon in the melts with relicts of 13C-enriched graphitized diamonds (probably generated from hydrothermal calcite veins in the subducting oceanic crust) reacted with the partial melts to form isotopically zoned nodule-like graphite aggregates. © 2005 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: BENI BOUSERA; CARBON ISOTOPES; GRAPHITE; RONDA; ULTRAMAFIC ROCKS